2011
DOI: 10.1089/jmf.2010.1529
|View full text |Cite
|
Sign up to set email alerts
|

(–)-Epigallocatechin-3-O-Gallate Augments Pentobarbital-Induced Sleeping Behaviors Through Cl Channel Activation

Abstract: This experiment investigated whether (-)-epigallocatechin-3-O-gallate (EGCG) (5-20 mg/kg, p.o.) has hypnotic effects and/or enhances pentobarbital-induced sleeping behaviors and whether these effects are mediated by γ-aminobutyric acid (GABA) receptors. EGCG prolonged sleeping time induced by pentobarbital (42 mg/kg, i.p.) and reduced sleeping latency induced by pentobarbital similarly to muscimol (0.2 mg/kg, i.p.), a GABA(A) receptor agonist in mice. EGCG also increased sleeping rate and sleeping time when co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…One is stimulant caffeine, and the other is EGCG which may be sedative. From our experiment, it was interesting that only EGCG from green tea augmented pentobarbital-induced sleeping time through Cl − channel activation ( Park et al ., 2011 ). This may suggest that EGCG counteracts caffeine-induced stimulant effects such as hyperactivity, arousal and anxiogenic effects ( Park et al ., 2010 ).…”
Section: Natural Products Which Have Proven To Be Effective For Sleepmentioning
confidence: 91%
“…One is stimulant caffeine, and the other is EGCG which may be sedative. From our experiment, it was interesting that only EGCG from green tea augmented pentobarbital-induced sleeping time through Cl − channel activation ( Park et al ., 2011 ). This may suggest that EGCG counteracts caffeine-induced stimulant effects such as hyperactivity, arousal and anxiogenic effects ( Park et al ., 2010 ).…”
Section: Natural Products Which Have Proven To Be Effective For Sleepmentioning
confidence: 91%
“…On the other hand, chronic treatment with polyphenolic green tea extracts enriched in EGCG decreased the expression of the GABAergic synaptic markers GAD67 and VGAT in the cortex of Ts65Dn mice (Souchet et al, 2015). Conversely, EGCG positively modulated GABA A -mediated transmission when administered acutely (Vignes et al, 2006; Park et al, 2011). Of note, a recently concluded clinical trial (TESDAD, NCT01699711) evaluating the efficacy of long-term green tea extract treatment on DS patients showed some behavioral improvements, although—as stated by the authors—below the threshold for clinical relevance in 2 out of 15 measured tests (de la Torre et al, 2016).…”
Section: Speculation For Future Directions In the Research On Ds And mentioning
confidence: 99%
“…(−)-Epigallocatechin-3-gallate ( Figure 8 ) is the most active flavanol contained in green tea, the product of Camellia sinensis (Theaceae). Park et al, [ 117 ] suggested that its anxiolytic and sedative effects are mediated by GABA A receptors. In their in vitro and in vivo experiments, (−)-epigallocatechin-3-gallate (5–20 mg/kg, p.o.)…”
Section: Phytochemicals With the General Anesthetic Activitymentioning
confidence: 99%